Illuminating the Dusty Universe: A Tribute to the Work of Bruce Draine - AAVV (Il Colle di Galileo, 2024)
Abstract. From catalyzing the formation of molecules, to building up planets, obscuring stellar light and tracing cosmic star formation rates, dust has an outsized impact on the astrophysics and observational properties of the Universe. Few have contributed more to illuminating our own understanding of the dusty universe than Prof. Bruce Draine of Princeton University. To celebrate the vision of Prof. Draine and assess our current view of astrophysical dust from different perspectives, including laboratory astrophysics, meteoritics, astrochemistry, optics and observational astronomy across the electromagnetic spectrum, 90 scientists from 18 countries spanning five continents gathered last autumn at the Garbasso Institute. The conference was an opportunity to highlight Prof. Draine’s past and ongoing work in this field as well as the enduring collaborations and friendships formed along the way. Arcetri has hosted Prof. Draine many times, over a period of almost 40 years, and he has spent many sabbaticals here, also writing part of his textbook “Physics of the Interstellar and Intergalactic Medium.”